2015
DOI: 10.18632/oncotarget.2868
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB signaling mediates acquired resistance after PARP inhibition

Abstract: PARP inhibitors are a class of promising anti-cancer drugs, with proven activity in BRCA mutant cancers. However, as with other targeted agents, treatment with PARP inhibitors generates acquired resistance within these tumors. The mechanism of this acquired resistance is poorly understood. We established cell lines that are resistant to PARP inhibitor by continuous treatment with the drug, and then used RNA sequencing to compare gene expression. Pathway analysis on the RNA sequencing data indicates that NF-κB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 30 publications
(47 reference statements)
0
47
0
Order By: Relevance
“…The affected cells then enter apoptosis. PARP inhibitor-resistant breast and ovarian cancer cell lines harboring BRCA1 mutation were used to study gene expression by RNA sequencing (249). Pathway analysis showed that ∼50% of the differentially expressed genes were NF-κBregulated genes and that TNFα was the upstream regulator of several of them.…”
Section: Poly-adenosine Diphosphate (Adp) Ribose Polymerase (Parp) Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The affected cells then enter apoptosis. PARP inhibitor-resistant breast and ovarian cancer cell lines harboring BRCA1 mutation were used to study gene expression by RNA sequencing (249). Pathway analysis showed that ∼50% of the differentially expressed genes were NF-κBregulated genes and that TNFα was the upstream regulator of several of them.…”
Section: Poly-adenosine Diphosphate (Adp) Ribose Polymerase (Parp) Inmentioning
confidence: 99%
“…It was also demonstrated that treatment of PARP inhibitor-resistant cells with bortezomib induced cell death to a greater extent than the parental cell line, confirming the involvement of the NF-κB pathway in the resistant phenotype. Bortezomib treatment increases PARP inhibitor sensitivity of the resistant cell lines, suggesting a possible therapeutic combination in the clinical setting (249).…”
Section: Poly-adenosine Diphosphate (Adp) Ribose Polymerase (Parp) Inmentioning
confidence: 99%
“…They intend to exploit synergistic effects of the agents or to overcome cytostatic resistance of the cancer cells. In the latter respect, ataxia telangiectasia and Rad3-related protein, mTOR, and NFκB pathway inhibitors were found to be effective [119,139,140].…”
Section: Open Questions and Future Directionsmentioning
confidence: 99%
“…Upregulation of the NF‐κB signaling pathway upon PARPi treatment is seen in ovarian cancer cell lines. Although the mechanism for such upregulation is not exactly determined but cotreatment with the NF‐κB and PARPi reversed the acquired resistance . Another approach to overcome the resistance for PARPi proposed a combinatorial therapy using ABT‐888 and vorinostat (a histone deacetylase inhibitor).…”
Section: Resistance To Parp Inhibitors: An Emerging Problem In Its CLmentioning
confidence: 99%
“…Although the mechanism for such upregulation is not exactly determined but cotreatment with the NF-κB and PARPi reversed the acquired resistance. 128 Another approach to overcome the resistance for PARPi proposed a combinatorial therapy using ABT-888 and vorinostat (a histone deacetylase inhibitor). Vorinostat sensitizes PARPi resistance cell lines to 6-thioguanine and this effect was due to increase in the phosphorylation status of Eukaryotic Initiation Factor 2 (eIF2α).…”
Section: Resistance To Parp Inhibitors: An Emerging Problem In Its CLmentioning
confidence: 99%